Contact tracing of health care workers as a part of health system strengthening: lessons learnt from field experience - Pathak, Vineet Kumar; Panigrahi, Sunil Kumar; Raj, Utsav; Giri, Anjan Kumar; Kujur, Anubhuti (International Journal Of Community Medicine And Public Health, 2023)
Health care workers (HCWs) are the frontline workers working tirelessly during the pandemic of coronavirus disease-2019 (COVID-19). The same HCW, after duty, is exposed to his/ her community which again increases the risk of infection. Hence, with an increased risk of exposure, we cannot afford to lose our frontline workers due to sickness or more. In the absence of any definitive antiviral treatment, unclear modes of transmission, burnout working hours, fatigue, societal stigma related to disease etc., a HCW is exposed to psychological distress and many a time develops an anxiety/panic condition which can increase the chances of work-place error and thus can increase the likelihood of infection. In this article, we have shared our experience with contact tracing among HCWs, what we have learned in the past two years, and proposed a way forward.